Implementasi GIS untuk Pemetaan UMKM Berbasis Mobile Menggunakan Metode A* di Sumenep - Haq, Nabil Huda Rizalul (JUSIFOR : Jurnal Sistem Informasi dan Informatika, 2025)
Sumenep Regency has great potential in culinary tourism, supported by rich local culture and the widespread presence of culinary MSMEs. However, the lack of integrated information and navigation systems hinders effective exploration of these destinations. This study aims to develop a mobile-based culinary MSME mapping application by integrating Geographic Information System (GIS) and the A Star (A*) algorithm. The system was developed using Flutter for the frontend and Laravel for the backend, with communication via RESTful API. Data were collected through observation, interviews, and literature study. The implementation results show that the application successfully displays MSME locations, calculates the shortest route in real-time, and assists users in quickly and accurately finding culinary spots. Black-box testing indicates that all system features function correctly. This application contributes to the digital promotion of local MSMEs and offers an innovative solution for culinary tourism development in the region.